Identification of an enhancer-like element in the 5' flanking region of the rat apolipoprotein A-I gene. - Chao, Y S (1988)
In order to study the expression of the apolipoprotein (apo) A-I gene, we have isolated and characterized the structural gene encoding rat apo A-I. The 5' flanking sequence of the apo A-I gene was placed upstream of the coding sequence of the bacterial chloramphenicol acetyl transferase (CAT) gene, such that the expression of CAT activity in cultured cells is under the control of the promoter and regulatory sequences of the rat apo A-I gene. By transient transfection, nucleotide deletion and substitution methods, it was demonstrated that the nucleotide sequences between -464 and -148 upstream from the start of transcription of the rat apo A-I gene are required for the expression of this gene in Hep G2 cells and that these sequences function with an enhancer-like activity.